A comparison of quality of life and psychological distress in heart transplantation patients at adult and pediatric ages. Issue 5 (8th May 2019) - Cavalli, Chiara; Tarzia, Vincenzo; Marini, Massimo; Gregori, Dario; Casella, Silvia; Bottio, Tomaso; Toscano, Giuseppe; Fraiese, Angela Pompea; Gambino, Antonio; Volpe, Biancarosa; Gerosa, Gino
Abstract: Background: The aim of the current study was to evaluate and compare the quality of life (QOL) and psychological status of adult patients who underwent heart transplant (HTx) at pediatric or adult ages. Methods: The population consisted of two groups: patients who received HTx after 18 years old and pediatrics who received HTx between the age of 1 and 18 years. At the time of the study, all patients were over 18 years old. QOL data were collected from patients using 36‐item Short‐Form Health Survey (SF‐36) and psychological distress by the Symptom checklist 90‐revised questionnaire (SCL‐90‐R). Results: A total of 232 HTx patients were evaluated; 217 were transplanted at an adult age and 15 at a pediatric one. QOL improved significantly in pediatrics patients in the general health perceptions subscale and physical pain subscale than adult patients. The Global Index of the psychological distress did not differ in the two groups, but the pediatric patients registered statistically significant higher scores on the interpersonal sensitivity symptom subscale (adult group 36 ± 0.42 vs pediatric group 81 ± 0.79), the hostility subscale (adult group m 39 ± 0.44 vs pediatric group 73 ± 0.76) and the paranoid ideation subscale (adult group 46 ± 0.46 vs pediatric group 96 ± 1.02). Conclusion: The pediatric heart recipients showed better quality of life, but they show marked sensitivity, hostility and paranoid ideation which increases the risk of mental distress and therefore their adherence to medical treatment.